Fostering competition in Thailand's telecommunications sector - Xavier, Patrick (Camford Publishing Ltd, 2010)
Purpose – The purpose of this paper is to use “best practice” regulatory principles to derive proposals for fostering competition in Thailand's telecommunications market. Design/methodology/approach – On-site research in Thailand was conducted, including interviews with a range of policy and regulatory agencies and telecommunications market participants. Findings – The paper finds that Thailand's relatively late start in applying pro-competitive regulation in the telecommunications sector presents an opportunity for installation of “regulatory leap-frogging” measures proposed by the paper. The concession regime that prevails in Thailand is a major obstacle resulting in “gridlock” of Thailand's efforts to develop competition in the telecommunications sector. The Thai Constitution prohibits the regulator from directly regulating telecommunications companies operating on the basis of concessions that were in place prior to the adoption of the new telecommunications law. The paper examines this problem and points to a solution. Another major problem is the protracted absence of the National Broadcasting Commission that has been given joint responsibility (along with the National Telecommunications Commission) for spectrum management. Accordingly, pressing decisions regarding spectrum management cannot be made. The paper concludes that the two Commissions be merged (especially in the face of convergence). The paper finds that Thailand needs to develop and implement a national strategy for the development of communications infrastructure, including a collaborative approach to infrastructure development.Originality/value – There are very few (if any) independent studies of policy and regulation of Thailand's telecommunications sector. More broadly, the paper indicates – by way of a case study – how “best practice” regulatory guidelines might be applied to enhance competition in developing countries.